Penyediaan Fasilitas Pendukung Protokol Kesehatan terhadap Pengalaman Berwisata, Keputusan Berkunjung, Kepuasan Pengunjung serta Dampaknya terhadap Citra Destinasi Wisata di Era New Normal: Studi Eksploratif - Kristiutami, Yuliana Pinaringsih; Pudin, Apip; Pirastyo, Swastono Putro (Media Wisata, 2023)
The living pattern mega shift happened because of the Covid-19 pandemic. The pattern shifting is rough and can be felt by everyone, especially in the tourism industry. Because of that, we need to conduct a study to find out the impact of the new normal era on the tourist experience, visiting decisions, tourist satisfaction, and the effect on the destination brand image. This study focused on the sociological aspect of tourism to observe the 1) tourist experience, 2) visiting decision process, 3) the satisfaction factor, and 4) the impact on the destination brand. The method used in this study is exploratory qualitative and uses data triangulation to analyze the data. The research instrument used in this study is observation, interview, and documentation. The total respondent of this study is 90 people chosen by the purposive sampling technique, and bring the final result of 87 valid respondents. The final result of this study is 1) 83,9% of respondent said that every destination has come with a good health protocol facility, 2) 86,2% said that the presence of the health protocol facility brings a positive visiting experience, 3) The visiting decision also influenced by the good health protocol facility but not to sign with only 68,96% respondent, 4) 81,6% respondent believed that their hope was fulfilling when their do the visit. And from that number, 55,17% said that their hope was fulfilled nicely, and 26,44% of respondent said that their hope was just quite fulfilled; 5) The brand issue related to the presence and the quality of the health protocol facility bring such a significant positive answer from 94,25% respondent.